Overexpression of OsNAC14 Improves Drought Tolerance in Rice - Shim, Jae Sung; Oh, Nuri; Chung, Pil Joong; Kim, Youn Shic; Choi, Yang Do; Kim, Ju-Kon (Frontiers in Plant Science, 2018)
Plants have evolved to have sophisticated adaptation mechanisms to cope with drought stress by reprograming transcriptional networks through drought responsive transcription factors. NAM, ATAF1-2, and CUC2 (NAC) transcription factors are known to be associated with various developmental processes and stress tolerance. In this study, we functionally characterized the rice drought responsive transcription factor OsNAC14. OsNAC14 was predominantly expressed at meiosis stage but is induced by drought, high salinity, ABA and low temperature in leaves. Overexpression of OsNAC14 resulted in drought tolerance at the vegetative stage of growth. Field drought tests demonstrated that OsNAC14 overexpressing transgenic rice lines exhibited higher number of panicle and filling rate compared to non-transgenic plants under drought conditions. RNA-sequencing analysis revealed that OsNAC14 overexpression elevated the expression of genes for stress response, DNA damage repair, defense related and strigolactone biosynthesis. In addition, chromatin immunoprecipitation analysis confirmed the direct interaction of OsNAC14 with the promoter of OsRAD51A1, a key component in homologous recombination in DNA repair system. Collectively, these results indicate that OsNAC14 mediates drought tolerance by recruiting factors involved in DNA damage repair and defense response resulting in improved tolerance to drought.